Telecommunications Reform in Malawi - Clarke, George R.G.; Gebreab, Frew A.; Mgombelo, Henry R. (World Bank, Washington, DC, 2014)
In 1998 the Government of Malawi decided to reform its telecommunications sector. Although the reform was ambitious in some ways, it was modest when compared with the most ambitious reforms adopted elsewhere in Sub-Saharan Africa. The two main accomplishments were splitting the incumbent fixed line monopoly, the Malawi Post and Telecommunications Corporation, into two companies-Malawi Telecommunications Limited (MTL) and Malawi Post Corporation (MPC)-and issuing two new cellular licenses to two new private entrants. In addition, the Government also established a new regulator which was separate from, but heavily dependent on, the Ministry of Information and liberalized entry in value-added and Internet services. However, the Government had neither privatized the fixed-line telecommunications operator nor introduced competition in fixed-line services by the end of 2002. Clarke, Gebreab, and Mgombelo discuss sector performance before reform, details of the reform, the political motivation for reform, and events in the five years following the reform. The reform yielded mixed results. Although cellular penetration and Internet use expanded dramatically following reform, prices increased, especially for cellular calls, and fixed-line penetration remains low by regional standards.